The Role of Students’ Self-Regulated Learning, Grit, and Resilience in Second Language Learning - Wang, Liang (Frontiers in Psychology, 2021)
It has been established that grit has a fundamental role in the learning and teaching process since gritty learners are more likely to take part in classroom activities and they are also motivated to deal with challenges in difficult circumstances. In addition, to guard against these hardships as well as self-control in responding to unpredicted circumstances, a similar construct arouses in positive psychology, called resilience that describes perseverance and emphasizes people’s abilities. Besides, language learners’ engagement and performance in the foreign or second language classroom can be improved through self-regulated learning which is viewed as one of the most inspected issues in learning and psychology. A present review has been conducted to scrutinize the relationship between language learners’ self-regulated learning and learners’ resilience and grit based on their positive theoretical relationship with educational success. Consequently, the issue of educator training and administrative training is illuminated through several aspects.